Pengaruh Motivasi Kerja Dan Kompensasi Terhadap Kinerja Karyawan Pada PT Hokky Bersama Di Gandaria Kota Jakarta Selatan - Doffa Wardana; Amirudin Amirudin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study was to determine the effect of Work Motivation and Compensation on Employee Performance at PT Hokky Bersama in Gandaria, South Jakarta City, both partially and simultaneously. The method used in this study is a quantitative method. The sampling technique used is saturated sampling, which uses a sample of 60 respondents. The data analysis technique used is statistical analysis with validity test, reliability test, classical assumption test, simple linear test, multiple linear regression test, coefficient of determination, hypothesis t test and hypothesis f test. The results of the study showed that Work Motivation has a significant effect on Employee Performance partially, indicated by the simple linear regression equation Y = 17.598 + 0.644X1 This is evidenced by the hypothesis test obtained t count> t table (7.983> 1.671) and strengthened by the ρ value <Sig.0.05 or significance <0.05 (0.000 <0.05). Compensation has a significant effect on Employee Performance partially indicated by the simple linear regression equation Y = 9.871 + 0.776X2 This is evidenced by the results of the hypothesis test obtained a calculated value of t> ttable (10.742> 1.671) and reinforced by the value of ρ value <Sig.0.05 or a significance value <0.05 (0.000 <0.05). The results of the study of Work Motivation and Compensation on Employee Performance at PT Hokky Bersama. Indicated by the multiple linear regression equation Y = 9.538 + 0.157X1 + 0.640X2 This is evidenced by the results of the hypothesis test simultaneously obtained a calculated value of f> ftable (59.437> 3.16) and reinforced by a significance value <0.05 (0.000 <0.05). The results of the coefficient determination test of the variables Work Motivation (X1) and Compensation (X2) have an influence on Employee Performance at PT Hokky Bersama. Thus Ho3 is rejected and Ha3 is accepted. This means that there is a significant simultaneous influence between Work Motivation (X1) and Compensation (X2) on Employee Performance (Y)..